Bridging Gaps in ESL Education: Challenges and Remedial Strategies for Present-Day Learners (Journal of Informatics Education and Research, 2025)
English has become the most widely used lingua franca in the world, creating significant challenges for those whose first language is not English, especially in academic and professional contexts. The influence of their original tongue frequently works as a barrier to learning proper English pronunciation, diction, and fluency because every learner has a unique linguistic background. In many sociolinguistic areas, English, a language of greater communication, commonly overlaps with mother tongues and regional dialects, resulting in identity negotiation and linguistic interference. In various educational environments, like those in and around Delhi, where language diversity may exacerbate sentiments of inferiority or marginalization in peer interactions, this overlap is particularly noticeable among students. In such instances, the job of an instructor transforms into that of a mentor, demanding a change away from conventional teaching methods and toward a more practical approach. The purpose of this study is to investigate the challenges that educators face when teaching English as a foreign language in India, and to provide to improve the teaching experience for of students as well as educators. It aims to provide insights that will be useful to scholars and researchers around the world.